Effect of degree of milling and kernel fragment size on the moisture desorption behavior of Pinilisa Rice at 47°C - Escoreal, Joanne Kathrine M.; Dumelod, Benelyn D. (Quezon City College of Home Economics, University of the Philippines Diliman, 2017)
In this study, the effect of degree of milling and fragment size on the moisture desorption behavior of Pinilisa rice at 47ºC was determined. The equilibrium moisture content (EMC) and equilibration time of different Pinilisa rice samples were determined at 47ºC over a water activity range of 0.02-0.96 using static gravimetric method. Using two-way ANOVA and post-hoc tests, the effect of degree of milling, fragment size and their interaction were tested at α = 0.05. The moisture desorption isotherm (MDI) of Pinilisa rice samples were also generated and its type was identified. Five model equations of moisture sorption isotherms (the Modified GAB (MGAB), Modified Halsey (MHAE), Modified Henderson (MHE), Modified Chung-Pfost (MCPE), and Modified Oswin Equation) were fitted to the experimental isotherm using non-linear regression and evaluated for goodness-of-fit using RSS, SEE, MRD and R2. The monolayer values were determined using the GAB and BET equation as well as the inflections points using the best-fit model. The MDIs of Pinilisa rice samples resembled the type II isotherm. The results also show that both degree of milling and fragment size significantly affect the EMC and equilibration time of Pinilisa rice samples and that their interaction is significant in most water activity levels. Definite trends of effects on both the EMC and equilibration time across all water activity levels were not observed. The MGAB model best fits more isotherms (dehulled ground, undermilled broken, and regular milled whole and ground), followed by the MCPE, MHAE and then MOE and MHE. The BET and GAB monolayer values, and first and second inflection points ranged from 3.21 to 4.55% MCdb, 2.81 to 6.67%MCdb, 0.11 to 0.30 and 0.65 to 0.86, respectively. Knowledge from this study are most useful in determining specifications for drying and storage operations of Pinilisa rice samples.
Thesis (B.S. Food Technology)--University of the Philippines Diliman.
Keywords: Rice -- Milling